Transformative Strategies for Inclusive Education to Eliminate Gender Bias and Strengthen Social Justice in Modern School Environments - Samsul Rizal; Tuti Isnani; Asep Mulyana; Nabil Akbar Tashawwufy (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study explores transformative strategies for inclusive education aimed at eliminating gender bias and strengthening social justice in modern school environments. The background highlights that despite the implementation of equality-oriented policies, gender disparities persist in Indonesian education—particularly in learning materials, teaching practices, and access to digital technology. The study aims to identify forms of gender bias, analyze inclusive learning strategies, and formulate a transformative educational model rooted in social justice. Using a qualitative literature review, data were collected from books, journal articles, policy documents, and international reports by UNESCO and UNICEF. The findings show that gender inequality manifests through stereotypes in textbooks, unequal participation in STEM fields, and digital discrimination. Effective strategies include integrating gender literacy into curricula, empowering teachers through training, and promoting collaboration among schools, governments, and communities. The study concludes that inclusive education transformation must combine curriculum reform, digital ethics, and social participation to achieve gender-equal learning environments.